Isoniazid-induced Choroidal Effusion: A Rare Presentation - Amit S. Nene; Manas Mengar; Onkar H. Pirdankar; Rajlaxmi Virkar; Pushpanjali Badole; Smitesh Shah (Delhi Journal of Ophthalmology)
The purpose is to report a rare case of isoniazid-induced choroidal effusion. A 62-year-old female who was under antitubercular treatment with isoniazid came with chief complains of diminution of vision in both eyes. Clinical evaluation, fundus photos, and B scan revealed choroidal detachment in both eyes. Discontinuation of antitubercular drug and posterior subtenon’s triamcinolone injection resulted in resolved choroidals. Health education about possible ocular side effects of isoniazid and periodic ophthalmic screening should be considered.